IMPLEMENTATION OF SELF-ASSESSMENT TO KNOW THE LEVEL OF STUDENT'S LEARNING MOTIVATION IN FOLLOWING ONLINE LEARNING - Fadilah Maharani; Deta Heriani; Anisa Fitri; Ahmad Walid (JISAE: Journal of Indonesian Student Assessment and Evaluation, 2021)
ABSTRACT This study aims to determine the level of student learning motivation by applying self-assessment in participating in online learning, and to provide an objective description of how the student's learning motivation is. This research uses a quantitative approach with a survey method. The research was conducted at Bengkulu State Islamic Institute involving 40 students in the Natural Science Tadris study program. Data collection techniques in this study used survey techniques with a Likert scale. The survey is made on google form so that it is easily accessible to students. The data analysis technique used in this study is to calculate the percentage of data from each indicator, then interpret the data presentation score and analyze each indicator in depth. The results of this study indicate that the learning motivation of students of the Tadris Study Program of Natural Science of the Agam Islam Negeri Bengkuli Institute is good, it is obtained from the percentage score of the motivation which amounts to 78.83%. This research is expected to be an evaluation of various parties in organizing online learning in tertiary institutions, especially those involving motivation. Keywords: self assessment, motivation, online learning